Are the twin or triple deficits hypotheses applicable to post-communist countries? - Hüseyin Şen; Ayşe Kaya (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​This study empirically examines the validity of the twin and triple deficits hypotheses using bootstrap panel Granger causality analysis and an annual panel data set of six post-communist countries (Russia, Poland, Ukraine, Romania, the Czech Republic, and Hungary) from 1994 to 2012. Our findings, based on panel data analysis under cross-sectional dependence and country-specific heterogeneity, support neither the twin deficits hypothesis nor its extended version, the triple deficits hypothesis, for any of the countries considered. In other words, we find no Granger-causal relationship between budget deficits and trade (or current account) deficits or among budget deficits, private savings-investment deficits, and trade deficits.
URN:NBN:fi:bof-201602251031
Keywords: E60; F30; F32; H62; 330